Transcutaneous Electrical Nerve Stimulation Uptake in Lowering Low Back Pain - Salsabil, Husna Arwa; Prasetya, Hanung; Murti, Bhisma (Indonesian Journal of Medicine, 2022)
Background: Low Back Pain (LBP) is a generalized pain from the second lumbar vertebra to the sacroiliac joint, and is generally a lifelong health disorder. LBP is often the cause of people feeling a decrease in ability in daily functional activities. Patients often complain of symptoms of pain, muscle spasms and impaired function. One of the interventions that can be used to reduce LBP is therapy using transcutaneous electrical nerve stimulation (TENS). TENS is a device used to relieve pain by stimulating nerves through electrodes transcutaneously. TENS is one of the modalities that can improve neuromuscular function or reduce pain and is very useful for patients with complaints of low back pain who experience pain and muscle weakness around the pelvis, trunk, and lower legs. LBP patient.Subject and Method: This study was a meta-analysis with the following PICO, population: low back pain patients. Intervention: administration of TENS. Comparison: not given TENS. Result: decreased pain. The articles used in this study were obtained from three databases, namely Google Scholar, Pubmed, and Science Direct. Keywords to search for articles “transcutaneous electrical nerve stimulation” OR “TENS” AND “reduction pain” OR “pain relief” AND “low back pain”. The articles included are full-text English with a randomized control trial study design from 2007 to 2022. Article selection was carried out using PRISMA flow diagrams. Articles were analyzed using the Review Manager 5.3 . application.Results: A total of 12 case studies from continental Europe, America and Asia were selected for systematic review and meta-analysis. It was found that giving TENS -0.67 times reduced pain in complaints of low back pain compared to not given TENS significantly (SMD = -0.67; 95% CI = -1.03 to -0.32; p = 0.002).Conclusion: Transcutaneous Electrical Nerve Stimulation reduces pain in low back pain patients.Keywords: Transcutaneous Electrical Nerve Stimulation, reduction pain, low back painCorrespondence: Husna Arwa Salsabil, Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Mobile: +6289611006503. Email: husna0105@gmail.com.Indonesian Journal of Medicine (2022), 07(01): 9-18https://doi.org/10.26911/theijmed.2022.07.01.02